What if scale breaks community? Rebooting audience engagement when journalism is under fire - Posetti, J; Simon, F; Shabbir, N (Reuters Institute for the Study of Journalism, 2019)
This report focuses on how digital-born news media navigate audience engagement in the context of both rapid developments in a digital media environment and significant political pressure, including the ‘weaponisation’ of social media to target and harass independent news organisations and individual journalists, along with their audiences. It is based on a detailed study of three news organisations in the process of actively redefining audience engagement. They are Rappler (the Philippines); Daily Maverick (South Africa); and The Quint (India) – all commercial news organisations of the Global South, whose public interest journalism has been recognised with top international industry awards. We find that, in response to the risks associated with various forms of what we’re calling ‘platform capture’, these news organisations are evolving, and are increasingly focused on forging deeper, narrower, and stronger relationships with audiences.